ANALISIS PRODUKSI DODOL KENTANG DI KECAMATAN SIULAK KABUPATEN KERINCI - Ray, Ray Evando; Etik Umiyati; Nurhayani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The purpose of this study was to determine and analyze the effect of venture capital, labor and raw materials on the production value of potato dodol in Siulak District, Kerinci Regency.. This study used a population consisting of 62 respondents of potato dodol SMEs business actors. Hypothesis testing was carried out using the F test and t test, with a significant (α) 5%. Data analysis using statistical data management software, namely SPSS 22.00 for windows. Based on the results of the study, it showed that the variables of working capital, labor and raw materials simultaneously affected the production value of potato dodol in Siulak District, Kerinci Regency. While the partial effect is that the variables of labor and raw materials have a significant effect on the production value of potato dodol in Siulak District, Kerinci Regency, while business capital has no significant effect on the production value of potato dodol in Siulak District, Kerinci Regency.